Convex Hemiepiphysiodesis: Posterior/anterior in-situ Versus Posterior-only With Pedicle Screw Instrumentation. Issue 8 (December 2016) - Bekmez, Senol; Demirkiran, Halil G.; Yilmaz, Guney; Akel, Ibrahim; Atilla, Pergin; Muftuoglu, Sevda Fatma; Yazici, Muharrem; Alanay, Ahmet
Abstract : Study Design: Experimental study. Background: Convex growth arrest (CGA) has been commonly used in the treatment of long-sweeping congenital deformities of the immature spine. As there are major drawbacks about the anterior procedure in the conventional CGA method, a new modification has been documented that using only posterior spinal approach with pedicle screw instrumentation. The aim of the study was to compare posterior-only CGA using pedicle screws with combined anterior/posterior in-situ CGA for the findings in histologic, radiologic, and manual palpation examinations in an immature pig model. Methods: Twelve 10-weeks old pigs were grouped into 2. In group 1, posterior-only, pedicle screw instrumented CGA was performed on the left side of L1-L4 vertebrae. In group 2, conventional combined posterior and anterior CGA was performed to the left side of L1-L4 vertebrae without instrumentation. All animals were killed twelve weeks after surgery. T11-L5 segments were en-bloc resected and radiologic, histologic, and manual palpation examinations were done. Results: Marked scoliotic (12.2±2.5 and 9.2±1.3 in group 1 and 2, respectively) and kyphotic (11.2±1.0 degrees for the group 1 and 12±5.2 degrees for the group 2, respectively) deformities were noted in both groups, which were caused by hemiepiphysiodesis effect. Anterior and posterior parts of group 2 and posterior part of group 1 demonstrated fusion in histologic and radiologic analyzes. In anterior part of the group 1, marked narrowing on the disk spaces and thinning of growth plates were noted in radiologicg examination, chondrocyte degeneration, and newly-formed bone trabeculae in disk-space were noted in histological examination. In manual palpation, no motion was detected in group 1 and motion was detected in only one segment of one animal in group 2. Conclusions: Anterior growth of the vertebrae can be controlled by application of posterior transpedicular screws and rod. Such an effect can eliminate the need for anterior surgical intervention in convex hemiepiphysiodesis procedures. Clinical Relevance: The instrumented CGA technique provides a satisfactory epiphysiodesis effect both anteriorly and posteriorly, as previously demonstrated by clinical studies.